Robust interfaces for mixed-timing systems. - Chelcea, T. (IEEE Transactions on VLSI systems)
This paper presents several low-latency mixed-timing FIFO (first-in-first-out) interfaces designs that interface systems on a chip working at different speeds. The connected systems can be either synchronous or asynchronous. The designs are then adapted to work between systems with very long interconnect delays, by migrating a single-clock solution by Carloni et al. (1999, 2000, and 2001) (for "latency-insensitive" protocols) to mixed-timing domains. The new designs can be made arbitrarily robust with regard to metastability and interface operating speeds. Initial simulations for both latency and throughput are promising.